Oral contraceptives and breast cancer: latest findings in a large cohort study. - Vessey, M. P. (Nature Publishing Group, 1989)
During the interval 1968-74, 17,032 women aged 25-39 years were recruited to the Oxford-Family Planning Association contraceptive study, more than half of whom were using oral contraceptives. These women have been followed up over the years and breast cancer has been diagnosed in 189 of them. We have analysed the available data in two ways. First, we have calculated standardised breast cancer incidence rates in non-users and users of oral contraceptives according to total duration of use, interval since first use, interval since last use, duration of use before first term pregnancy and duration of use before age 25. Secondly, we have conducted case-control within cohort analyses to examine the possible effects of different types of pill and to search for evidence of a latent effect of oral contraceptive use before first term pregnancy on breast cancer risk. We have found no evidence of any adverse effect of oral contraceptive use on the risk of breast cancer in this study. There was, however, little exposure to the pill before first term pregnancy among the participants and virtually no such exposure at a very young age (i.e. below 20 years). Accordingly, the results of this study strengthen the evidence that oral contraceptive use by mature women does not increase breast cancer risk, but add little to the uncertainty about the effects of early use.